Emergent properties of a non-physiological computational model of tumour growth - Pantziarka,Pan (PeerJ PrePrints, 2015)
NEATG is a simple non-physiological tumour growth model which displays emergent properties which are analogous to a number of characteristics common to physical tumour growth. NEATG employs a novel dual-scale evolutionary algorithm which models both cell-autonomous and non-cell autonomous behaviours. The components of the model are outlined briefly, with reference to the core algorithm and data structures. Experimental results are presented which illustrate the behaviour of the model under different evolutionary scenarios, including homeostasis, tumour growth and a number of anti-tumour interventions. In particular the system is used to explore the impact of cytotoxic interventions, (analogous to high-dose chemotherapy), with respect to adaptive responses and evolutionary change. Finally, a number of avenues for further development of the system are discussed.
Keywords: cancer; evolution; computational model; carcinogenesis; tissue organisation field theory; somatic mutation theory; modelling; genetic algorithm